Pengaruh Corporate Governance, Profitabilitas, Ukuran Perusahaan, Leverage, Dan Kualitas Audit Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Pada Tahun 2014 - Mayasari, Mayasari; Al-Musfiroh, Hamnah (Jurnal Akuntansi Dan Bisnis Indonesia (JABISI), 2020)
The goal of this study is to determine the effect of institutional ownership, profitability, firm size, leverage and audit quality towards the tax evasion. In order to find out the influence between two or more variables, the study uses the descriptive and the causal associative approaches. The sixty six manufacturing companies (basic industry and chemical sector) registered in the 2014 Indonesian Stock Exchange (BEI) become the population in this study, and the purposive sampling is conducted to take the 39 samples of the study. The result shows two things. The first outcome demonstrates that the institutional ownership, profitability, leverage, and audit quality do not possess significant influence towards the tax evasion whilst the second one shows that the firm size has the significant influence towards the tax evasion.